Job Performance Motivation of Teachers in Educational Institutions under the Office of the Vocational Education Commission, Bangkok - สุริยวรากุล พงศธร; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study the job performance motivation of teachers in educational institutions; 2) to compare the job performance motivation of teachers classified by personal factors; and 3) to establish guidelines for promoting the job performance motivation of teachers in educational institutions under the Office of the Vocational Education Commission, Bangkok. The research sample consisted of teachers selected through Stratified Random Sampling followed by Simple Random Sampling. The research instrument was a 5-point Likert scale questionnaire, with an Index of Item-Objective Congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient (Cronbach’s Alpha) of 0.99. Data were analyzed using frequency, percentage, mean, standard deviation, t-test, F-test (One-way ANOVA), and content analysis. The results revealed that: 1) The job performance motivation of teachers was overall at a high level. When considering each aspect, it was found to be at a high to highest level. The aspect with the highest mean was Responsibility, followed by Achievement, while the aspect with the lowest mean was Salary. 2) The comparison of job performance motivation classified by gender showed no significant difference overall. However, when considering individual aspects, the aspect of job status showed a significant difference at the .05 level of significance. Regarding age, educational level, and work experience, no significant differences were found. 3) The guidelines for promoting job performance motivation indicated that administrators should assign tasks based on individual expertise, coupled with providing recognition and establishing transparent career advancement paths; develop the management system through participatory administration and welfare provision to ensure work-life balance; and improve the work environment to facilitate performance while using Professional Learning Community (PLC) processes to foster positive relationships within the organization.